Kontekstualisasi Gagasan Fiqh Indonesia T.M. Hasbi Ash-Shiddieqy (Telaah atas Pemikiran Kritis Yudian Wahyudi) - Mansur Mansur (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
Agree and disagree is an integral part when talking about the idea of Fiqh Indonesia TM Hasbi Ash-Shiddiqy (fiqh is determined based on thepersonality and character of Indonesia). Critical review conducted by Yudian Wahyudi about the idea ofFiqh Indonesia is very important to be understood thoroughly inorderto align the proportionality debate andat the same time the idea of FiqhIndonesiaHasbi contextualization. The description in this paper is the result of reading the author entirely to the works of Yudian Wahyudi to reviewthe idea of FiqhIndonesiaHasbi, especiallya work entitled Hasbi's Theory of Ijtihadin the Context of Indonesian Fiqh(2007).